SiC-enhanced road microcrack self-repairing microcapsule capable of absorbing waves and increasing temperature as well as preparation method and application of SiC-enhanced road microcrack self-repairing microcapsule
Through SiC-enhanced absorbable warming microcapsules, combined with the dual mechanisms of absorption warming and micro-crack tip stress, the problem of low micro-crack repair efficiency under low temperature conditions in the prior art is solved, and efficient self-repairing effect of asphalt pavement is achieved.
Patent Information
- Application Number
- CN202411779466.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to quickly repair micro-cracks on asphalt pavement under low temperature conditions, and the single-mechanical induction mode of the heat-induced method is not efficient.
The microcrack self-healing microcapsules for road-enhanced with SiC enhanced absorbable wave-increasing heating are self-healing microcapsules through emulsifiers, compound regeneration agents, SiC powders, polyethylene glycol, high methyl etherified melamine-formaldehyde resins, and ethylene dichloride The combination of alcohol and curing agent has excellent absorption and heating characteristics and efficient self-healing performance.
In microwave radiation environment, SiC-enhanced microcapsules can quickly heat up, significantly improving the repair efficiency of asphalt microcracks and improving the self-healing performance of the road surface.
Smart Images

Figure CN119430725A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of asphalt pavement repair materials, and in particular to a SiC-enhanced road microcrack self-repairing microcapsule capable of absorbing waves and heating up, and a preparation method and application thereof. Background Art
[0002] Asphalt pavement is widely used due to its advantages such as smooth surface and comfortable driving. However, asphalt pavement is prone to fatigue cracking and microcracks during long-term use. Under the influence of traffic load and external environment, microcracks will gradually deepen to form macro cracks, which will affect the performance and service life of the pavement. Studies have shown that asphalt, as a viscoelastic material, has certain self-healing properties, but this self-healing ability is not enough to repair microcracks in a timely and effective manner. Therefore, road researchers have developed various technologies to enhance the self-healing properties of asphalt, such as induction heating and microcapsule repair, to improve the self-healing properties of asphalt pavements. Among them, microcapsule self-healing technology is considered to be an effective method to improve self-healing performance because it does not require energy input and additional equipment.
[0003] Microcapsules are core-shell structures composed of capsule walls and regenerants. The regenerants are released by triggering stress at the tip of microcracks to improve the self-healing properties of asphalt or asphalt binder. Therefore, microcapsules should contain a higher content of regenerants and maintain integrity during the mixing and compaction process of the mixture. However, in actual application, the passive stress-induced mode of releasing regenerants only by triggering stress at the tip of microcracks cannot guarantee that the regenerants can quickly fill cracks under low temperature conditions. Studies have found that the repair efficiency of regenerants for microcracks is positively correlated with temperature, and increasing the external temperature is conducive to the diffusion and filling of regenerants; at the same time, temperature can enhance the diffusion of asphalt molecules, and increasing the external temperature is conducive to promoting the self-healing of surrounding microcracks. Therefore, the use of thermal induction to achieve the induced release of regenerants has become a major research hotspot in microcapsule self-healing technology.
[0004] At present, road researchers have conducted in-depth research on the single-mechanism induction mode of microcrack tip stress and heating induction, but there is still a lack of thermal dual-induction microcapsules with better efficiency of dual-mechanism effects of wave absorption heating + microcrack tip stress. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a SiC-enhanced self-repairing microcapsule for road microcracks that can absorb waves and heat up, and a preparation method and application thereof. The SiC-enhanced self-repairing microcapsule for road microcracks that can absorb waves and heat up provided by the present invention has good thermal stability and mechanical properties, and at the same time has excellent wave absorption and heating characteristics, and can efficiently repair road microcracks.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is a SiC-enhanced road microcrack self-repairing microcapsule capable of absorbing waves and heating up, wherein the raw materials include the following components by weight:
[0008] 2-4 parts of emulsifier, 9-12 parts of compound regeneration agent, 0.1-1 parts of SiC powder, 0.01-0.05 parts of polyethylene glycol, 6-8 parts of high methyl ether melamine-formaldehyde resin, 0.5-1 parts of ethylene glycol and 6-8 parts of curing agent.
[0009] The second technical solution of the present invention is a method for preparing the above-mentioned SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing waves and heating up, comprising the following steps:
[0010] Step 1. Using emulsifier and compound regeneration agent as raw materials, preparing emulsion;
[0011] Step 2. Mixing SiC powder and polyethylene glycol and grinding to obtain modified SiC;
[0012] Step 3. Evenly mix the high methyl etherified melamine-formaldehyde resin, ethylene glycol and water to obtain a prepolymer solution;
[0013] Step 4. uniformly dispersing the modified SiC into the prepolymer solution to obtain a composite capsule wall prepolymer solution;
[0014] Step 5. Add the composite capsule wall prepolymer solution dropwise into the emulsion, and then add a curing agent for curing to obtain the SiC-reinforced microcrack self-repairing microcapsules for road use that can absorb microwaves and heat up.
[0015] The third technical solution of the present invention is a self-repairing asphalt mixture, the raw materials of which include the above-mentioned SiC-enhanced road microcrack self-repairing microcapsules that can absorb waves and heat up.
[0016] A fourth technical solution of the present invention is the use of the above-mentioned SiC-enhanced road microcrack self-repairing microcapsules that can absorb waves and heat up in the self-repair of microcracks in asphalt pavements.
[0017] The present invention discloses the following technical effects:
[0018] The SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing and heating up by microwaves provided by the present invention can achieve a heating rate of 4.07°C / min under a microwave radiation environment, have excellent microwave absorbing and heating characteristics, and further improve the efficiency of the microcapsules in repairing asphalt microcracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is a process flow chart of the preparation of SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing waves and raising temperature in the present invention;
[0021] Figure 2 This is a finished product of the SiC-enhanced road-use microcrack self-repairing microcapsules capable of absorbing waves and raising temperature prepared by the present invention;
[0022] Figure 3 This is a scanning electron microscope image of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and raising temperature, prepared in Example 3 of the present invention;
[0023] Figure 4 This is a particle size distribution diagram of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and heating up prepared in Example 1 of the present invention;
[0024] Figure 5 The fluorescence microscopic morphology images of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and heating up prepared in Examples 1-4 and Comparative Examples 1 and 2 of the present invention; wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, (e) is Comparative Example 1, and (f) is Comparative Example 2;
[0025] Figure 6 This is a thermogravimetric curve of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and raising temperature prepared in Example 3;
[0026] Figure 7 The self-healing effect comparison diagram of asphalt mixture added with self-repairing microcapsules for micro cracks in asphalt pavement prepared in Example 3, Comparative Examples 1 and 2, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, and (c) is Example 3. DETAILED DESCRIPTION
[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0028] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] The first aspect of the present invention provides a SiC-enhanced road microcrack self-repairing microcapsule capable of absorbing waves and heating up, wherein the raw materials include the following components by weight:
[0033] 2-4 parts of emulsifier, 9-12 parts of compound regeneration agent, 0.1-1 parts of SiC powder, 0.01-0.05 parts of polyethylene glycol, 6-8 parts of high methyl ether melamine-formaldehyde resin, 0.5-1 parts of ethylene glycol and 6-8 parts of curing agent.
[0034] In some embodiments of the present invention, the emulsifier is sodium dodecyl sulfate; the compound regeneration agent is a mixture of waste vegetable oil, epoxidized soybean oil and aromatic oil; the particle size of the SiC powder is 0.5-2.0 μm; the molecular weight of the polyethylene glycol is 200; and the curing agent is a mixture of sodium chloride, resorcinol and ammonium chloride.
[0035] The present invention adopts waste vegetable oil, epoxidized soybean oil (EOS) and aromatic oil as raw materials for capsule core materials. Waste vegetable oil is not only inexpensive but also has good compatibility with asphalt and can effectively restore microcracks; epoxidized soybean oil (EOS) is used as a plasticizer to reduce the viscosity of aged asphalt; aromatic oil has better fluidity and can supplement the light components in aged asphalt.
[0036] In the present invention, if the particle size of SiC powder is too large, the adhesion is low, the weight is heavy, and it is not easy to adhere to the surface of the microcapsule wall, or adhere to the surface of the microcapsule, causing the microcapsule structure to be unstable and easy to break; if the particle size is too small, it adheres to the microcapsule wall, the capsule wall is not rough enough, and the adhesion to asphalt is poor after being added to the asphalt mixture.
[0037] When the molecular weight of polyethylene glycol is less than 600, the polyethylene glycol is liquid, and when it is greater than 600, it gradually becomes a waxy solid. Polyethylene glycol with a lower molecular weight is often used as a solid dispersant. Therefore, polyethylene glycol with a molecular weight less than 600 is selected for modifying SiC.
[0038] In some embodiments of the present invention, the composite regeneration agent is a mixture of waste vegetable oil, epoxidized soybean oil and aromatic oil in a mass ratio of 5:3:2; the mass ratio of sodium chloride, resorcinol and ammonium chloride is (95-100):(5-8):(5-8).
[0039] The second aspect of the present invention provides a method for preparing SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and heating up, comprising the following steps:
[0040] Step 1. Using emulsifier and compound regeneration agent as raw materials, preparing emulsion;
[0041] Step 2. Mixing SiC powder and polyethylene glycol and grinding to obtain modified SiC;
[0042] Step 3. Evenly mix the high methyl etherified melamine-formaldehyde resin, ethylene glycol and water to obtain a prepolymer solution;
[0043] Step 4. uniformly dispersing the modified SiC into the prepolymer solution to obtain a composite capsule wall prepolymer solution;
[0044] Step 5. Add the composite capsule wall prepolymer solution dropwise into the emulsion, and then add a curing agent for curing to obtain the SiC-reinforced microcrack self-repairing microcapsules for road use that can absorb microwaves and heat up.
[0045] In some embodiments of the present invention, in step 1, the preparation method of the emulsion is specifically as follows: after the emulsifier is uniformly dispersed in water, a constant temperature swelling treatment is performed, and then a compound regeneration agent is added to perform a high-speed shear treatment to obtain the emulsion. The temperature of the constant temperature swelling treatment is 30°C and the time is 1 hour; the shear rate of the high-speed shear treatment is 3500r·min -1 , the shearing time is 20-30min.
[0046] In some embodiments of the present invention, in step 2, a grinding aid is also added during the grinding; the grinding aid is SiC sand and ethanol. The present invention does not impose any special restrictions on the amount of the grinding aid, and a conventional selection by a person skilled in the art can be used, for example: the mass ratio of SiC powder, SiC sand and ethanol is (2-5):1:1.
[0047] In some embodiments of the present invention, in step 2, the grinding time is 1-1.5h.
[0048] In some embodiments of the present invention, in step 2, after the grinding is completed, it also includes the steps of drying and sieving; the drying temperature is 70° C., and the sieving is through a 90-mesh sieve.
[0049] The present invention uses polyethylene glycol to modify SiC so that the polyethylene glycol forms a coating on the surface of SiC, thereby improving the surface properties of SiC powder, effectively alleviating the agglomeration of SiC during the in-situ polymerization process, and making it more evenly dispersed in the capsule wall material. The present invention adds SiC to the capsule wall material, which can significantly improve the thermal stability and mechanical properties of the capsule wall material.
[0050] In some embodiments of the present invention, in step 3, the mass ratio of the high-methylated melamine-formaldehyde resin to water is (45-63):1000.
[0051] In the present invention, in step 4, the present invention does not specifically limit the dispersion method of uniformly dispersing the modified SiC into the prepolymer solution, and a technical means well known to those skilled in the art may be selected, such as ultrasonic dispersion.
[0052] In some embodiments of the present invention, the rate of dripping is 1.5-3 ml·min -1 .
[0053] In some embodiments of the present invention, in step 5, after adding the curing agent, the pH value is adjusted to 4.0-4.5, and then the temperature is increased from room temperature to 1.5°C min -1The temperature is raised to 70-80°C in a water bath at a heating rate of 2-3 hours and stirred at a constant temperature for 2-3 hours. In the present invention, the reagent for adjusting the pH value to 4.0-4.5 is a 10-20wt% acetic acid solution; the stirring rate is 900-1000r·min -1 .
[0054] In some embodiments of the present invention, after the curing is completed, the steps of washing, filtering and drying the obtained suspension to obtain a solid product are also included; the drying temperature is 80-100°C and the time is 1 hour. The present invention can remove the core material and SiC powder that are not coated on the surface of the microcapsule by washing.
[0055] A third aspect of the present invention provides a self-repairing asphalt mixture, the raw materials of which include the SiC-enhanced wave-absorbing and temperature-raising road microcrack self-repairing microcapsules described in the above technical solution.
[0056] A fourth aspect of the present invention provides an application of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing waves and heating up as described in the above technical solution in the self-repair of microcracks in asphalt pavements.
[0057] In order to better understand the present invention, the following examples are combined to further illustrate the content of the present invention, but the content of the present invention is not limited to the following examples. The synthesis process of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and heating is shown in the figure. Figure 1 shown.
[0058] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0059] Example 1
[0060] The preparation method of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing waves and raising temperature provided in this embodiment is as follows:
[0061] (1) Preparation of emulsion: 0.64 g sodium dodecyl sulfate was added to deionized water, stirred until completely dispersed, and swollen in a constant temperature water bath at 30 °C for 1 h. Then, 9.94 g of a composite regeneration agent (mass ratio of waste vegetable oil, epoxidized soybean oil EOS and aromatic oil = 5:3:2) was added and stirred at 3500 r / min. -1 The emulsion was obtained by high-speed shearing for 30 min;
[0062] (2) Modification of SiC: 0.64 g SiC powder, 0.28 g SiC sand and 0.28 g ethanol were mixed, 0.03 g polyethylene glycol was added, and the mixture was fully ground on a planetary mill for 1 h. After drying at 70 °C, the mixture was ground through a 90-mesh sieve to obtain modified SiC.
[0063] (3) Preparation of prepolymer solution: 6.33 g of high methyl etherified melamine-formaldehyde resin, 0.63 g of ethylene glycol and 10 mL of deionized water were mixed and stirred thoroughly to obtain a prepolymer solution;
[0064] (4) Preparation of SiC modified capsule wall: slowly adding the modified SiC in step (2) to the prepolymer solution in step (3), and ultrasonically dispersing for 50 minutes to obtain a composite capsule wall prepolymer solution;
[0065] (5) Synthesis of microcapsules: The composite capsule wall prepolymer solution in step (4) was added dropwise to the emulsion in step (1), and a composite curing agent aqueous solution (sodium chloride 6.31 g, resorcinol 0.32 g, ammonium chloride 0.32 g, deionized water 32 g) was added at 3 ml / min. -1 Slowly add 10 wt% acetic acid solution at a rate of 1.5 ℃·min, adjust the pH value to 4.5, and control the water bath temperature at 1.5 ℃·min -1 The rate of heating is gradually increased from 15℃ to 70℃ at 900-1000r·min -1 The suspension was stirred at a high speed for 2 hours to obtain a microcapsule suspension, which was washed with deionized water and petroleum ether in turn and then filtered, and the solid product was collected and dried at 100°C for 1 hour to obtain SiC-enhanced microcrack self-repairing microcapsules for road use that can absorb microwave heating. (The amount of SiC in this embodiment is 10% of the capsule wall mass)
[0066] The particle size of the obtained SiC-enhanced road microcrack self-repairing microcapsules that can absorb microwave heating is statistically analyzed. Figure 4 It can be seen that the particle size distribution is between 42-76 μm, mainly concentrated between 50-60 μm, and the particle size distribution is relatively uniform.
[0067] Example 2
[0068] The preparation method of the SiC enhanced wave-absorbing and temperature-raising road microcrack self-repairing microcapsules provided in this embodiment is the same as that in Example 1, except that 0.64g of SiC powder is replaced with 0.48g of SiC powder. (The amount of SiC in this embodiment is 7.5% of the mass of the capsule wall)
[0069] Example 3
[0070] The preparation method of the SiC enhanced wave-absorbing and temperature-raising road microcrack self-repairing microcapsules provided in this embodiment is the same as that in Example 1, except that 0.64g of SiC powder is replaced with 0.32g of SiC powder. (The amount of SiC in this embodiment is 5% of the mass of the capsule wall)
[0071] Example 4
[0072] The preparation method of the SiC enhanced wave-absorbing and temperature-raising road microcrack self-repairing microcapsules provided in this embodiment is the same as that in Example 1, except that 0.64g of SiC powder is replaced with 0.16g of SiC powder. (The amount of SiC in this embodiment is 2.5% of the mass of the capsule wall)
[0073] Comparative Example 1
[0074] This comparative example provides a road microcrack self-repairing microcapsule, which is prepared by an in-situ polymerization method. The preparation method is the same as that of Example 1, except that the addition of SiC is omitted.
[0075] Comparative Example 2
[0076] This comparative example provides a road microcrack self-repairing microcapsule, which is prepared by interfacial polymerization. The preparation method is as follows:
[0077] ① Preparation of aqueous phase: Add PVA emulsifier to deionized water and stir with a glass rod until fully dissolved to prepare an aqueous phase with a PVA mass fraction of 0.4%;
[0078] ② Preparation of oil phase: Mix oil-soluble reaction monomer isophorone diisocyanate (IPDI) and asphalt regeneration agent (the same as the compound regeneration agent in Example 1) in a mass ratio of 3:5 and disperse them evenly to obtain an oil phase;
[0079] ③ Preparation of emulsion: Mix the oil phase and the water phase in a mass ratio of 4:1, and prepare the asphalt regeneration agent emulsion after emulsification using a high-speed shearing machine. The shearing speed is 5000RPM and the shearing time is 5min.
[0080] ④ Microcapsule molding: The emulsion was transferred to a beaker and stirred at a speed of 200RPM using a mechanical stirrer in a water bath to prevent the microcapsules from sticking to each other. At the same time, the catalyst dibutyltin dilaurate (DBTDL) was added dropwise, and the amount of DBTDL added was 10% of the mass of IPDI. The temperature was then controlled at 70±0.5°C for 3 hours to terminate the reaction, and the reaction system was slowly cooled to room temperature;
[0081] ⑤ Microcapsule separation: The microcapsule emulsion obtained in the previous step is transferred to a centrifuge tube, and then centrifuged at 10000RPM for 3 minutes using a high-speed centrifuge. The microcapsules floating on the upper part of the centrifuge tube are then taken out, washed with deionized water and centrifuged again. This process is repeated 3 times to rinse the microcapsules clean. The microcapsules obtained from the last centrifugation are dried in a drying oven at 60°C for 1 hour to obtain microcapsules.
[0082] Figure 3 This is a fluorescence microscopic image of the self-repairing microcapsule prepared in Example 3. Figure 5The fluorescence microscopic morphology of the self-healing microcapsules prepared in Examples 1-4 and Comparative Examples 1 and 2. From (a) to (e), it can be seen that the capsule wall of the microcapsules prepared after adding SiC is rougher and denser, and the particle size is uniform; the particle size of the microcapsules without adding nano-carbon powder is too large, and the capsule wall surface is smooth but not dense enough. Figure (f) shows that the microcapsules prepared by the method of Comparative Example 2 have uneven particle sizes, and the capsule wall surface is smooth but not dense enough.
[0083] Test example: performance test
[0084] 1.1 Mechanical properties test:
[0085] The microcapsules prepared in Example 3 of the present invention were tested by using the nanoindentation test technology, and the specific steps are as follows: 1) Use a glass cutter to cut a glass slide into a square size of 1 cm×1 cm; 2) Apply the crystal glue evenly on the cut glass slide, and use a glue spreader to make the glue layer thin and flat; 3) Sprinkle a small amount of microcapsule sample on the above glass slide before the glue solidifies; 4) Wrap the above sample to be tested with plastic wrap and put it in a culture dish at room temperature for 24 hours. After the glue is completely cured, fix the glass slide with the microcapsules in the same way on the loading platform of the nanoindentation test for subsequent tests. The test results of the mechanical properties of the microcapsules in the embodiment and the comparative example are shown in Table 1.
[0086] Table 1 Young's modulus and nanohardness test results
[0087]
[0088] The results of the nanoindentation test show that the nanohardness and Young's modulus of the SiC modified microcapsules provided by the present invention are higher than the corresponding mechanical parameters of the unmodified microcapsules (Comparative Example 1), indicating that using SiC as a modifier for the microcapsules can effectively improve the mechanical properties of the microcapsules and make them have more excellent anti-deformation ability.
[0089] 1.2 Thermal stability test
[0090] The microcapsules prepared in Example 3 of the present invention, as well as the undoped melamine formaldehyde resin (capsule wall material) and the asphalt regeneration agent (capsule core material) were tested by thermogravimetric analysis. The test results are as follows: Figure 6 (In the figure, the microcapsules represent the microcapsules of Example 3).
[0091] The results show that when the temperature is below 200℃, the modified microcapsules hardly experience thermal weight loss, and the mass loss is only 4.257%; when the temperature is 300℃, the mass retention rate of the modified microcapsules can still reach 90%; when the temperature exceeds 350℃, significant mass loss occurs. This shows that the addition of SiC modifier significantly improves the thermal stability of the microcapsules and effectively delays the damage and consumption of the core material by the external high temperature environment.
[0092] The microcapsules prepared in Examples 1, 2, and 4 were subjected to the same thermal stability test as in Example 1. The test results were similar to those in Example 1. When the temperature was below 200°C, the microcapsules hardly experienced thermal weight loss, with a mass loss of only 4.257%. When the temperature was 300°C, the mass retention rate of the modified microcapsules could still reach 90%. When the temperature exceeded 350°C, significant mass loss occurred. This indicates that the addition of the SiC modifier significantly improved the thermal stability of the microcapsules and effectively delayed the damage and consumption of the core material by the external high temperature environment.
[0093] 1.3 Basic performance indicators of capsule core materials
[0094] Table 2 Basic performance indicators of capsule core materials
[0095]
[0096]
[0097] 1.4 Thermodynamic performance test
[0098] An infrared thermal imager was used to observe the temperature rise of the microcapsules prepared in Example 3 of the present invention and Comparative Example 1 at different microwave times. The specific steps were as follows: 1) 10 g of microcapsules were repeatedly rinsed with petroleum ether, then dispersed in anhydrous ethanol, and then placed in a 60°C oven for 2 h to evaporate the remaining water; 2) the microcapsules were evenly spread on a glass slide 1 cm 2 3) placing the glass slide in a microwave heating cabinet for microwave heating; 4) after the microwave heating, using an infrared thermal imager to obtain an infrared thermal image of the microcapsule. The test results are shown in Table 3.
[0099] Table 3 Temperature rise characteristics of microcapsules under different microwave heating times
[0100]
[0101] The results show that the SiC-modified microcapsules for road microcrack self-repairing that can absorb microwaves and increase temperature prepared by the present invention have excellent microwave absorption and temperature increase characteristics. The temperature of the microcapsules that have not been modified by SiC has almost no change under microwave radiation environment, indicating that SiC can give the microcapsules the function of absorbing microwaves and increasing temperature.
[0102] In summary, the present invention adopts SiC as a modifier for road microcapsules through chemical reaction design to prepare road microcapsules with high capsule core content and uniform particle size, which has a significant improvement effect on the road thermal stability, mechanical properties and self-healing properties of asphalt mixture.
[0103] 1.5 Semicircular split loading-healing-loading test
[0104] The microcapsules in Example 3 and Comparative Example 1 were prepared into microcapsule asphalt mixture specimens, and the self-healing performance of the microcapsules in AC-16 and SMA-13 asphalt mixtures was tested. The specific steps are as follows: 1) The prepared semicircular specimen was placed in a low-temperature test box at 0°C for 2 hours, and the first splitting test was performed, and the critical load at this time was recorded as P0; 2) The split semicircular specimen was wrapped and fixed with a mold, and then placed in a microwave radiation environment for healing. After the healing was completed, it was placed in a 0°C environmental box again for 2 hours; 3) The fixed mold was removed and step 1 was repeated until the specimen was completely broken, and the critical load at this time was recorded as P1.
[0105] The healing index (HI) was used to quantify the healing effect of microcapsules on asphalt mixture.
[0106]
[0107] Figure 7 The results show that the increase in the amount of microcapsules (the amount of microcapsules is 0-12% of the mass of mineral powder in asphalt mixture) can significantly enhance the self-healing performance of asphalt mixture. The SiC-modified microcrack self-repairing microcapsules for road use that can absorb microwaves and heat up in Example 3 of the present invention can significantly improve the self-healing performance of asphalt mixture under microwave radiation conditions.
[0108] 1.6 The performance of the road microcrack self-repairing microcapsules modified with nano-carbon powder and capable of absorbing waves and heating up provided by the present invention compared with general microcapsules is shown in Table 4.
[0109] Table 4
[0110]
[0111] The test method for the capsule core content is:
[0112] The core content of microcapsules is determined by solvent extraction. First, the microcapsules are crushed several times to destroy the capsule wall structure and allow the regeneration agent to leak out completely. Then, the microcapsules that have been washed and cleaned several times are filtered and dried to obtain the residue of their capsule wall, which is the mass of the composite capsule wall of the microcapsule sample being tested. The core mass of the microcapsule sample being tested is the mass difference between the microcapsule sample and the composite capsule wall. Therefore, the core content of the microcapsule (R c ) can be calculated by the formula:
[0113]
[0114] Where: R c —Microcapsule core content, %;
[0115] m c —Microcapsule core mass, g;
[0116] m0—total mass of microcapsules, g;
[0117] m s —Microcapsule wall mass, g.
[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A SiC-enhanced microcrack self-repairing microcapsule for road use capable of absorbing microwaves and heating up, characterized in that: The raw materials include the following components by mass: 2-4 parts of emulsifier, 9-12 parts of compound regeneration agent, 0.1-1 parts of SiC powder, 0.01-0.05 parts of polyethylene glycol, 6-8 parts of high methyl ether melamine-formaldehyde resin, 0.5-1 parts of ethylene glycol and 6-8 parts of curing agent.
2. The SiC-enhanced road microcrack self-repairing microcapsule capable of absorbing microwaves and heating up according to claim 1 is characterized in that: The emulsifier is sodium dodecyl sulfate; the compound regeneration agent is a mixture of waste vegetable oil, epoxidized soybean oil and aromatic oil; the particle size of the SiC powder is 0.5-2.0 μm; the molecular weight of the polyethylene glycol is 200; and the curing agent is a mixture of sodium chloride, resorcinol and ammonium chloride.
3. A method for preparing the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and heating up as claimed in claim 1 or 2, characterized in that: The following steps are involved: Step 1. Using an emulsifier and a compound regenerating agent as raw materials, preparing an emulsion; Step 2. Mixing SiC powder and polyethylene glycol and grinding to obtain modified SiC; Step 3. Evenly mix the high methyl etherified melamine-formaldehyde resin, ethylene glycol and water to obtain a prepolymer solution; Step 4. uniformly dispersing the modified SiC into the prepolymer solution to obtain a composite capsule wall prepolymer solution; Step 5. Add the composite capsule wall prepolymer solution dropwise into the emulsion, and then add a curing agent for curing to obtain the SiC-reinforced microcrack self-repairing microcapsules for road use that can absorb microwaves and heat up.
4. The method for preparing SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing microwaves and heating up according to claim 3, characterized in that: In step 1, the preparation method of the emulsion is specifically as follows: after the emulsifier is uniformly dispersed in water, a constant temperature swelling treatment is performed, and then a compound regeneration agent is added to perform a high-speed shear treatment to obtain the emulsion.
5. The method for preparing SiC-enhanced microcapsules for road microcrack self-repair capable of absorbing waves and heating up according to claim 3, characterized in that: In step 2, a grinding aid is also added during the grinding; the grinding aid is SiC sand and ethanol.
6. The method for preparing SiC-enhanced microcapsules for road microcrack self-repair capable of absorbing microwaves and heating up according to claim 3, characterized in that: In step 5, after adding the curing agent, the pH value is adjusted to 4.0-4.5, and then the mixture is stirred at a constant temperature of 70-80° C. for 2-3 hours.
7. A self-repairing asphalt mixture, characterized in that: The raw materials include the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing waves and heating up as described in claim 1 or 2.
8. Use of the SiC-enhanced road microcrack self-repairing microcapsules capable of absorbing waves and heating up as claimed in claim 1 or 2 in the self-repair of microcracks in asphalt pavements.